Sistem Kontrol Otomatis Berbasis IoT dan Sel Surya Untuk Budidaya Jamur Tiram di Desa Selorejo, Jombang - Lila Yuwana; Susilo Indrawati; Sudarsono Sudarsono; Niniet Indah Arvitrida; Iim Fatimah; Diky Anggoro (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
Lila Yuwana*1, Susilo Indrawati2, Sudarsono3, Niniet Indah Arvitrida4, Iim Fatimah5, Diky Anggoro61,2,3,5,6Departemen Fisika, Institut Teknologi Sepuluh Nopember4Departemen Teknik dan Sistem Industri, Institut Teknologi Sepuluh Nopember*e-mail: lila@physics.its.ac.id1, susilo_i@physics.its.ac.id2 , sudars29@gmail.com3, arvietrida@gmail.com4, iim.fatimah.its@gmail.com5, anggorodiky@gmail.com6 Received: 31 Mei 2021/ Accepted: 16 Juni 2021  Abstract Pleurotus ostreatus cultivation has been developed using wood sawdust as a planting medium in Selorejo Village, Mojowarno District, Jombang Regency, East Java. Previous research, sawdust can function very well as a growing medium for oyster mushrooms, which is indicated by the abundance of yields. In addition, the use of sawdust can also overcome the problem of abundant waste from the furniture industries in Selorejo Village. In this community service that will be carried out, it aims to create an internet-based or IoT (Internet of Things) and solar cell-based control system as a resource for the entire system. The IoT system designed and built in abdimas is used to see the development of ostreatus mushrooms in the mushroom house through a webcam that is integrated with the system. Furthermore, through this IoT, humidity and temperature settings can be done anywhere through the android application and internet browser. The power system that uses solar cells in this service is taking into account the limited electrical power in the mushroom house in Selorejo Village, Mojowarno Jombang. All systems that are designed and will be built in this service are portable, in other words, they can be easily moved around. With this service, it is hoped that Micro, Small and Medium Enterprises (MSMEs) in ostreatus cultivation can increase the efficiency of the ostreatus mushroom growing process because monitoring the process of growing ostreatus mushrooms can be done anywhere and anytime, through an integrated IoT system. In addition, it is hoped that other MSMEs can adopt the automation system for controlling humidity and temperature for ostreatus mushroom cultivation based on IoT and solar cells. Key words: IoT (Internet of Things), solar cells, mushroom houses, ostreatus mushrooms, sensors and monitoring